Pemanfaatan lidimatika sebagai media pembelajaran matematika pada konsep perkalian di kelas III sekolah dasar - Mega Krisdiana; Siti Siti Malihah; Ila Rosmilawati (TIRTAMATH: Jurnal Penelitian dan Pengajaran Matematika, 2022)
The purpose of study is to find out how to use lidimatika as a media for learning mathematics in the multiplication concept in grade III elementary school. The benefits of this study are expected to contribute to the improvement of mathematics learning in the multiplication concept in elementary schools. This study uses a quantitative research design. In this study using a quasi-experimental method using one of the models, namely the nonequivalent control group design. The results of this research are that the learning outcomes of third grade elementary school students in multiplication material can be improved through the use of lidimatika media. This is evidenced from the results of the posttest that have been obtained between the experimental class using lidimatika media and the control class using conventional methods indicating that there is a fairly clear difference in values with the acquisition of an average score of the experimental class being 89 and the control class being 69. It was also carried out hypothesis testing using the Mann Whitney test obtained an Asymp (2-tailed) value of 0.001 which value if seen based on the basics of decision making, then the value is less than 0.05 then H1 is acceptable and indicates an increase in student learning outcomes by using lidimatika media.